2009
DOI: 10.1007/s11250-009-9467-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium avium subsp. paratuberculosis in tissue samples of cattle and buffaloes

Abstract: Tissue samples were collected at random from cattle (Bos taurus) and buffalo (Bubalus bubalis) from an abattoir of the district of Lahore and were analyzed for the presence of Mycobacterium avium subsp. paratuberculosis and Mycobacterium bovis through acid-fast staining and polymerase chain reaction (PCR). Body condition of animals and diarrhea were recorded. Most of the animals were emaciated. Diarrhea was noticed in 15.6% of buffaloes and 19.2% of cattle. Intestinal pathology was observed in 29% of buffaloes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
(20 reference statements)
4
8
0
1
Order By: Relevance
“…It might be due to the presence of other bacteria of tuberculosis because in our study only M. bovis and M. tuberculosis was differentiated by PCR. Similar results were also obtained by (Khan et al 2010) that ZN staining showed the AFB presence in 17.4% intestinal and 16.4% in lymph node tissue of buffalo, while PCR confirmed 12.8% in intestinal and 12.4% in lymph node sample positive for Paratuberculosis, which show higher number of positive results by microscopy than PCR. Moreover staining microscopy could not permit differentiation between species of MTB complex, only PCR methods can differentiate between them.…”
Section: Sensitivity and Specificity Of Different Techniquessupporting
confidence: 86%
“…It might be due to the presence of other bacteria of tuberculosis because in our study only M. bovis and M. tuberculosis was differentiated by PCR. Similar results were also obtained by (Khan et al 2010) that ZN staining showed the AFB presence in 17.4% intestinal and 16.4% in lymph node tissue of buffalo, while PCR confirmed 12.8% in intestinal and 12.4% in lymph node sample positive for Paratuberculosis, which show higher number of positive results by microscopy than PCR. Moreover staining microscopy could not permit differentiation between species of MTB complex, only PCR methods can differentiate between them.…”
Section: Sensitivity and Specificity Of Different Techniquessupporting
confidence: 86%
“…Prevalence of M. paratuberculosis in suspect Johne's disease dairy cattle by fecal culture was reported to be 50% in Egypt and 41% by culture or 32% by ELISA in Brazil (Salem et al, 2005;Ristow et al, 2007). Meta-analysis of results from buffalo suspected of Johne's disease in Pakistan and India were M. paratuberculosis positive in 12% of cases (95%CI 11-15, I 2 0%) by PCR, 5% (2-10, I 2 0%) by ELISA and 7% (0-27, I 2 99%) by visual confirmation (Sivakumar et al, 2006;Khan et al, 2010;Sikandar et al, 2012). Suspected Johne's disease in beef and dairy cattle from Europe and Asia were M. paratuberculosis positive in 16.8% of cases (10.9-23.7, I 2 91%) by PCR and culture (Branciari et al, 2008;Kaur et al, 2010;Khan et al, 2010;Munster et al, 2011).…”
Section: Paratuberculosis Infection In Animalsmentioning
confidence: 99%
“…Meta-analysis of results from buffalo suspected of Johne's disease in Pakistan and India were M. paratuberculosis positive in 12% of cases (95%CI 11-15, I 2 0%) by PCR, 5% (2-10, I 2 0%) by ELISA and 7% (0-27, I 2 99%) by visual confirmation (Sivakumar et al, 2006;Khan et al, 2010;Sikandar et al, 2012). Suspected Johne's disease in beef and dairy cattle from Europe and Asia were M. paratuberculosis positive in 16.8% of cases (10.9-23.7, I 2 91%) by PCR and culture (Branciari et al, 2008;Kaur et al, 2010;Khan et al, 2010;Munster et al, 2011). Studies of suspect caprine Johne's disease cases from Europe yielded a meta-analysis M. paratuberculosis prevalence of 24.6% (14.2-36.8, I 2 55%) by ELISA (Hartnagel, 2000;Stau et al, 2012).…”
Section: Paratuberculosis Infection In Animalsmentioning
confidence: 99%
“…Cattle, buffaloes, sheep, and goats are the most effected specie of domestic animals (Rosseels and Huygen, 2008;Singh et al, 2013;Khan et al, 2010). In wild animals almost all ruminants get infected including giraffe, deer (de Lisle and Collins 1995) and wild goats.…”
Section: Host Speciesmentioning
confidence: 99%